2019
DOI: 10.3390/nano9020156
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Vacancy Tuned Carbon Honeycomb

Abstract: Carbon honeycomb (CHC) has great application potential in many aspects for the outstanding mechanical properties. However, the effect of both defects and temperature on the mechanical properties are far from reasonable understanding, which might be a huge obstacle for its promising applications as engineering materials. In this work, we investigate the effect of vacancy-type defect, which is inevitably exists in material, on the mechanical properties of CHC via reactive molecular dynamics simulations. The mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…All studies in this paper were performed by MD simulations based on the Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) package [31]. In order to describe the interatomic force between carbon atoms, we used the adaptive intermolecular reactive empirical bond order (AIREBO) potential function, which was widely used in the interaction between carbon structure atoms, such as graphene [32], carbon nanotube [33] and CHC [34].…”
Section: Methodsmentioning
confidence: 99%
“…All studies in this paper were performed by MD simulations based on the Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) package [31]. In order to describe the interatomic force between carbon atoms, we used the adaptive intermolecular reactive empirical bond order (AIREBO) potential function, which was widely used in the interaction between carbon structure atoms, such as graphene [32], carbon nanotube [33] and CHC [34].…”
Section: Methodsmentioning
confidence: 99%
“…The CHC showed higher tensile strength and bigger ultimate tensile strain along the cell-axis direction as the temperature decreased. As our previous work illustrated [32], ultimate tensile strength of CHC was about 23 GPa in the zigzag direction and 22 GPa in the armchair direction at 300 K. The comparison of the stress–strain curves of CHC from this work and DFT calculations [24] is plotted in Supplementary Figure S1 with the same scale of axis. Results obtained from MD simulations were slightly smaller than that obtained from DFT calculations.…”
Section: Resultsmentioning
confidence: 66%
“…But the comprehensive theoretical studies of CHs [9,[16][17][18][19][20][21][22][23] proved their superb strength and stability. This strength remains at a high level but tunable with different cell sizes [17,24] and crucially depends on defectness of CH structures [25]. The mechanical simulations [9] showed that the Young's modulus of the structures is de-termined solely by the density of the hinges, and deformations are localized, similar to that of macroscopic honeycombs.…”
Section: Theory Of Chs and Important Applicationsmentioning
confidence: 98%